Progesterone Inhibits Estrogen-Induced Cyclin D1 and cdk4 Nuclear Translocation, Cyclin E- and Cyclin A-cdk2 Kinase Activation, and Cell Proliferation in Uterine Epithelial Cells in Mice - Tong, Wei (American Society for Microbiology, 1999)
The response of the uterine epithelium to female sex steroid hormones provides an excellent model to study cell proliferation in vivo since both stimulation and inhibition of cell proliferation can be studied. Thus, when administered to ovariectomized adult mice 17β-estradiol (E(2)) stimulates a synchronized wave of DNA synthesis and cell division in the epithelial cells, while pretreatment with progesterone (P(4)) completely inhibits this E(2)-induced cell proliferation. Using a simple method to isolate the uterine epithelium with high purity, we have shown that E(2) treatment induces a relocalization of cyclin D1 and, to a lesser extent, cdk4 from the cytoplasm into the nucleus and results in the orderly activation of cyclin E- and cyclin A-cdk2 kinases and hyperphosphorylation of pRb and p107. P(4) pretreatment did not alter overall levels of cyclin D1, cdk4, or cdk6 nor their associated kinase activities but instead inhibited the E(2)-induced nuclear localization of cyclin D1 to below the control level and, to a lesser extent, nuclear cdk4 levels, with a consequent inhibition of pRb and p107 phosphorylation. In addition, it abrogated E(2)-induced cyclin E-cdk2 activation by dephosphorylation of cdk2, followed by inhibition of cyclin A expression and consequently of cyclin A-cdk2 kinase activity and further inhibition of phosphorylation of pRb and p107. P(4) is used therapeutically to oppose the effect of E(2) during hormone replacement therapy and in the treatment of uterine adenocarcinoma. This study showing a novel mechanism of cell cycle inhibition by P(4) may provide the basis for the development of new antiestrogens.